Spectral Characterization and Biological Activities of Metal Complexes of Cu(II), Ni(II) and Co(II) with Tridentate a-Amino-1-indole Propionic Acid Based Ligand - Rai, Amit; Sharma, Ashish (Asian Journal of Chemistry, 2012)
Four novel Schiff base metal complexes of Cu(II), Ni(II) and Co(II) have been synthesized from a new Schiff base ligand derived from salicylaldehyde and a-amino-1-indole propionic acid. The ligand and its complexes have been characterized on the basis of elemental analysis, magnetic susceptibility, UV, IR, 1H NMR and 13C NMR spectral studies, as well as conductivity data. On the basis of spectral studies, for Co(II) complex tetragonal and Cu(II) and Ni(II) complex, octahedral geometry has been proposed. The data indicate that most of the metal complexes have higher antimicrobial activity than the free ligand against E. coli, Salmonella, P. aeruginosa and S. aureus.